PENGARUH IKLAN DAN TAGLINE TERHADAP MINAT BELI PADA Tiket.Com. INDONESIA - Rizky Hediyanti; Nuruni Ika Kusuma W (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Currently Indonesia has been experiencing a pandemic of Covid-19, a pandemic is evenly distributed globally so that it requires people to do their activities day-to-day to remain at home only. Thus this then the increase in digital services, especially e-commerce is rapidly increasing. Increased service digital in the field of e-commerce is made also of interest high consumer purchasing on e-coommerce one of them. The purpose of performing this research is to observe whether your ad is and the tagline effect on buying interest in Tiket.com. The population in this research is the people who see the ad and tagline Tiket.com Indonesia. This study applies non-probability sampling in the sampling of the research as well as adopting a purposive sampling technique. There were 66 respondents then the data collected from the respondents can be analyzed with Partial Least Square ( PLS ). This study obtained the existence of a positive influence in the buying interest Tiket.com based on ads provide a positive influence on buying interest, the tagline also give the influence of yan positively to purchase intention on Tiket.com Indonesia